Adaptasi Lansia Dalam Memenuhi Tugas Perkembangan Psikososial - Novellia Gita Nurani; Desi Desi; Sri Suwartiningsih (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
The elderly have a fairly crucial developmental task, namely having to adapt to changes physically, psychologically, socially and spiritually. Good adaptation will produce a good quality of life as well. In the theory of psychosocial development, the quality of life of the elderly will be seen in their success in achieving self-integrity or even despair (ego-integrity vs despair). This study discusses how the elderly adapt at the Panti Wredha Salib Putih Nursing Home in fulfilling their developmental tasks. Qualitative descriptive method was applied in this research. Participants were determined using a purposive sampling technique with the criteria of elderly participants aged 65 years and over, living in a nursing home, elderly who are physically and psychologically healthy, not on full bedrest, able to speak clearly and there were five elderly involved in this study. Data were collected using interview techniques with the help of an interview guide consisting of semi-structured questions on the process of adaptation and psychosocial development of ego-integrity vs despair. As a result, the adaptation of the elderly in fulfilling psychosocial developmental tasks includes the attainment of happiness in the elderly, acceptance of themselves and others, adaptation of the behavior and spirituality of the elderly. In conclusion, psychosocial adaptation, psychologically the elderly want to adjust and the elderly do not feel pressured or the reciprocal relationship between the elderly and the environment is comfortable and socially the elderly can accept and be accepted by friends. These experiences can be positively felt by the elderly in their old age, this can be a factor in the success of the elderly in fulfilling psychosocial development tasks so that they enter a state of ego-integrity.